Sharp inequality of Jackson–Stechkin type and widths of functional classes in the space \( L_2 \) - Langarshoev, Mukhtor Ramazonovich (Eurasian Mathematical Journal, 2014)
For classes of differentiable periodic functions, defined by means of generalized moduli of continuity \( Ω_m(f, t) \), satisfying the condition \( ( _0^h Ω_m^2/m(f(r), t) dt )^m/2 ≤ Φ(h) \), where \( m N \), \( r Z_+ \), \( h > 0 \) and \( Φ \) is a given majorant, under certain restrictions on the majorant, the exact values of various \( n \)-widths in the space \( L_2 \) are calculated.